A water-polydimethylsiloxane liquid lens for variable focus experiments in an undergraduate laboratory - Añonuevo, Johannes F (Archīum Ateneo, 2019)
Fluidic lenses offer tunability and flexibility that are not available with conventional solid lenses. The development of a variable focus lens has the potential for replacing bulky optical systems and allows the miniaturization of imaging optics used in digital cameras and mobile phone cameras. In this paper, a liquid lens platform for use in an undergraduate laboratory setting is presented. A variable lens is prepared by injecting water into bulk polydimethylsiloxane (PDMS) that remains uncured in its fluid state. We report the tunable focusing ability of this simple liquid lens system and analyze the change in focal length as a function of injected water volume. The water-PDMS interface acts as a diverging lens, in agreement with ray tracing analysis based on curvature and refractive indices. Variable focal lengths are measured with an optical set-up employing a helium-neon laser and a solid converging lens with focal length = 2.5 cm. By increasing the water volume from 0.05 to 0.30 ml, we are able to tune the focal length from -6.5 mm to -10.6 mm. Lens geometry remains spherical as the curvature of the lens changes with the addition of water. Our experiments coincide with a simple theoretical framework for a thick lens immersed in a medium. The water-PDMS lens is a promising component of basic and advanced experiments in an undergraduate optics course.